2017
DOI: 10.1021/acs.analchem.7b02129
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hydrogenation of Boron-Doped Diamond Electrodes by Cathodic Reduction

Abstract: Boron-doped diamond (BDD) has attracted much attention as a promising electrode material especially for electrochemical sensing systems, because it has excellent properties such as a wide potential window and low background current. It is known that the electrochemical properties of BDD electrodes are very sensitive to the surface termination such as to whether it is hydrogen- or oxygen-terminated. Pretreating BDD electrodes by cathodic reduction (CR) to hydrogenate the surface has been widely used to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 43 publications
2
63
0
4
Order By: Relevance
“…In 2010, Salazar‐Banda et al ., based on the CV and EIS responses of the [Fe(CN) 6 ] 3−/4− redox pair, recommended the following galvanostatic CPT in a 0.5 mol L −1 H 2 SO 4 aqueous solution: −1 A cm −2 for 9 s, i. e . a q pt value of −9 C cm −2 ; interestingly, a similar value of q pt (−9.25 C cm −2 ) was indicated by Kasahara et al . as being the most effective condition for the activation of a BDDE in a 0.1 mol L −1 H 2 SO 4 aqueous solution by applying −5 V vs .…”
Section: Electroanalytical Applications Of Electrochemically Pretreatsupporting
confidence: 76%
See 2 more Smart Citations
“…In 2010, Salazar‐Banda et al ., based on the CV and EIS responses of the [Fe(CN) 6 ] 3−/4− redox pair, recommended the following galvanostatic CPT in a 0.5 mol L −1 H 2 SO 4 aqueous solution: −1 A cm −2 for 9 s, i. e . a q pt value of −9 C cm −2 ; interestingly, a similar value of q pt (−9.25 C cm −2 ) was indicated by Kasahara et al . as being the most effective condition for the activation of a BDDE in a 0.1 mol L −1 H 2 SO 4 aqueous solution by applying −5 V vs .…”
Section: Electroanalytical Applications Of Electrochemically Pretreatsupporting
confidence: 76%
“…showed that BDD surfaces do not need to be highly hydrogenated to ensure that a reversible voltammetric behavior is obtained for the [Fe(CN) 6 ] 3−/4− redox system. Immediately after, Kasahara et al . reported that, for a fixed value of the pretreatment electric charge, q pt (−9.25 C cm −2 ), the attained degree of hydrogenation of the BDDE surface was higher when the CPT was performed using an acidic solution (pH=0.9).…”
Section: Different Approaches To Electrochemical Pretreatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different surface terminations of BDDs show various electrochemical responses towards redox species. This enables the selective detection of specific target compounds [54]. Ivandini et al [55] reported that oxalic acid could be determined only at hydrogen-terminated BDD surface.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity of BDD can be controlled from semiconducting to superconducting by adjusting the boron concentration, and this has can be used to influence the electrochemical properties. In addition, the electrochemical properties of BDD are also affected by several factors including the amount of sp 2 carbon impurity, the crystal orientation,, and the surface termination . Therefore, we can design BDD electrodes appropriate for a diverse range of applications …”
Section: Introductionmentioning
confidence: 99%